PROJECT BASED LEARNING UNTUK MENGEMBANGKAN KREATIVITAS MAHASISWA MERANCANG MEDIA INFORMASI BK MELALUI MEDIA SOSIAL - Ahmad Rofi Suryahdikusumah; Arizona Arizona (Journal of Innovative Counseling : Theory, Practice, and Research, 2018)
The research aims to create the greatest project based learning session in developing the student's creativity in designing the media information via social media. Research methods the research using the actions taken to the student practice field, creativity is reflected upon response followers social media designed by subject. Research conducted in seven cycle that includes a brainstroming, designing, executiing, and final reflection. The results showed 1) brainstroming is most important session in project based learning to develop creativity, 2) After the implementation of project based learning, students ' creativity in designing the media information by social media is on transformation level.